2021
DOI: 10.26721/spafajournal.2021.v5.650
|View full text |Cite
|
Sign up to set email alerts
|

History of Jakarta's Chinatown: The Role of the City Gate as a Transition Area and a Starting Point in the Spatial Transformation from the First Chinatown to the Renewal Phase | Sejarah Pecinan Jakarta: Peran Pintu Gerbang Kota Sebagai Area Transisi dan Titik Awal dalam Transformasi Spasial Pecinan Pertama ke Fase Pembaharuan

Abstract: In the history of Jakarta, Chinatown played a significant role to the formation of the city. The Chinatown area accompanied Jakarta along its journey and has been around since the city was still known as Batavia. The Chinese were among the actors who played a major role in the formation of urban space when Batavia began to develop. After four centuries, Jakarta’s Chinatown, which is now known as the Glodok area, continues to exist and is a bustling commercial area. The research conducted tries to dig further i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In 1619, Jan Pieterszoon Coen led the VOC in their attempt to destroy Jakarta and connect the Chinese community to the city [12]. Coen saw the benefits of establishing connections with the Chinese, who played a vital role in trade, providing essential goods, and helping with marketing.…”
Section: History Of the Chinese Community In Jakartamentioning
confidence: 99%
See 1 more Smart Citation
“…In 1619, Jan Pieterszoon Coen led the VOC in their attempt to destroy Jakarta and connect the Chinese community to the city [12]. Coen saw the benefits of establishing connections with the Chinese, who played a vital role in trade, providing essential goods, and helping with marketing.…”
Section: History Of the Chinese Community In Jakartamentioning
confidence: 99%
“…Abdurrahman Wahid, which resulted in the restoration of freedom for the population to engage in various activities related to Chinese culture, including tradition, beliefs, use of language, and customs. This significant milestone for the Chinese community in Indonesia was marked by the emergence of new celebrations and activities related to Chinese religion and culture in public spaces, as well as movements to re-establish the Pecinan area and other cultural elements within the urban space [12]. The diversity and cultural contributions of the Chinese community in Jakarta were recognized and appreciated, promoting a more inclusive and vibrant cityscape.…”
Section: History Of the Chinese Community In Jakartamentioning
confidence: 99%
“…Basically, Mayne [4] uses the corrected cone resistance (qt) to obtain OCR while Rahardjo et al [5] uses the pore pressure ratio (Bq). Mayne's [4] approach is mainly expressed in Equation (2). Equation ( 2) is originally proposed by Mayne et al [6].…”
Section: Overconsolidated Ratiomentioning
confidence: 99%
“…According to UNESCO [1], in the 14 th century, Kota Tua (previously named Sunda Kelapa) was a major trading port. Since then, the city population rapidly increased by the migration of the Chinese population and other European traders [2]. Kagabu et al [3] showed that the groundwater pumping for residential and industrial water supply in Jakarta increased exponentially following the increase of Jakarta's population from approximately 100,000 in 1900 to more than 9 million in 1995.…”
Section: Introductionmentioning
confidence: 99%